2022
DOI: 10.1002/anie.202213368
|View full text |Cite
|
Sign up to set email alerts
|

Hewettite ZnV6O16 ⋅ 8H2O with Remarkably Stable Layers and Ultralarge Interlayer Spacing for High‐Performance Aqueous Zn‐Ion Batteries

Abstract: Aqueous Zn‐ion batteries (ZIBs) are promising candidates for grid‐scale energy storage because of their intrinsic safety, low‐cost and high energy‐intensity. Vanadium‐based materials are widely used as the cathode of ZIBs, especially A2V6O16 ⋅ nH2O (AVO, A=NH4+, Na, K). However, AVO suffers from serious dissolution, phase transformation and narrow gallery spacing (∼3 Å), leading to poor cycling stability and rate capability. Herein, we unveiled the root cause of the performance degradation in the AVO cathode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…35 The rate performance of V 2 O 5 @rGO-1.5 cathode is also better than some of previously reposted materials (Supplementary Fig. 14b), such as VO 2 -PC (82.6 mAh g − 1 at 20 A g − 1 ), 27 VPMX73 (282.2 mAh g − 1 at 3 A g − 1 ), 46 ZVO (167 mAh g − 1 at 15 A g − 1 ), 47 Zn 0.25 V 2 O 5 •nH 2 O (183 mAh g − 1 at 6 A g − 1 ), 43 MnVO (214 mAh g − 1 at 8 A g − 1 ), 31 Ni 0.25 V 2 O 5 •nH 2 O (164 mAh g − 1 at 5 A g − 1 ), 48 NVO/CNTs (203 mAh g − 1 at 4 A g − 1 ), 49 NaCaVO (154 mAh g − 1 at 5 A g − 1 ), 45 and…”
Section: Energy Conversion and Storage Behaviorsmentioning
confidence: 85%
“…35 The rate performance of V 2 O 5 @rGO-1.5 cathode is also better than some of previously reposted materials (Supplementary Fig. 14b), such as VO 2 -PC (82.6 mAh g − 1 at 20 A g − 1 ), 27 VPMX73 (282.2 mAh g − 1 at 3 A g − 1 ), 46 ZVO (167 mAh g − 1 at 15 A g − 1 ), 47 Zn 0.25 V 2 O 5 •nH 2 O (183 mAh g − 1 at 6 A g − 1 ), 43 MnVO (214 mAh g − 1 at 8 A g − 1 ), 31 Ni 0.25 V 2 O 5 •nH 2 O (164 mAh g − 1 at 5 A g − 1 ), 48 NVO/CNTs (203 mAh g − 1 at 4 A g − 1 ), 49 NaCaVO (154 mAh g − 1 at 5 A g − 1 ), 45 and…”
Section: Energy Conversion and Storage Behaviorsmentioning
confidence: 85%
“…For example, both Nazar's team and our team showed that the presence of water as a solvent can increase the interlayer distance of V 2 O 5 · n H 2 O and V 3 O 7 · n H 2 O from 10 Å to 13 Å. 8,15,16,19 In Zn 2+ -based electrolytes that use pure acetonitrile as a solvent, the capacity of V 3 O 7 ·H 2 O is approximately 150 mA h g −1 since only zinc ions undergo reversible insertion/extraction during charge and discharge. However, when the electrolyte is switched to a water-based electrolyte, the capacity increases to 400 mA h g −1 due to proton insertion.…”
Section: Introductionmentioning
confidence: 90%
“…Many studies have demonstrated that water plays a crucial role in the performance of cathodes in ZIBs. 11,14–16 For example, our previous investigation utilized density functional theory (DFT) calculations to reveal that the presence of water in interlayers plays a crucial role in creating a smooth electrostatic environment between V 2 O 5 sheets. 17 This facilitates facile Zn 2+ diffusion due to the combined effects of “charge shielding” and the interaction between O in H 2 O and Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, researchers have proposed various strategies, including nanostructure design, , composites with conductive polymers, preintercalation, and defect engineering, to improve the electrochemical performance of δ-MnO 2 cathodes. In particular, the preintercalation strategy has proven to be a fundamental and highly effective approach for enhancing the capacity, cycle stability, and rate capability of a δ-MnO 2 cathode. , Preintercalated ions or molecules play a crucial role in increasing the interlayer spacing, facilitating ion transfer, and serving as “structural pillars” to prevent structural collapse. Meanwhile, preintercalation can efficiently fine-tune the electronic structure of the host materials, leading to significant acceleration of electron-transfer processes. Various ions and molecules have been previously investigated, including alkali ions, , NH 4 + , tetramethylammonium, Cu 2+ , Zn 2+ , Ba 2+ , La 3+ , Sn 4+ , Mo 4+ , and polyaniline . Chao et al incorporated Ba 2+ ions as interlayer pillars into δ-MnO 2 , which expanded the interlayer spacing from 0.63 to 0.70 nm, hence improving the Zn 2+ intercalation kinetics and enhancing the structural stability of δ-MnO 2 .…”
Section: Introductionmentioning
confidence: 99%